1996
DOI: 10.1007/bf00120491
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoadrenergic overactivity and lipid metabolism

Abstract: Epidemiological studies have identified high heart rates as a risk factor for coronary heart disease mortality, and heart rate was found to correlate with the severity of coronary atherosclerosis. Heart rate was positively correlated with serum concentrations of total cholesterol, triglycerides, and non-HDL cholesterol. Since heart rate responds sensitively to sympathoadrenergic activity, it was hypothesized that catecholamines play a crucial role in the unfavorable lipid alterations. In addition to influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…ANS dysregulation is reported to have a direct effect on BP regulation and lipid metabolism via circulating (nor) epinephrine (63)(64)(65)(66)(67). However, also more indirect ways are reported, for instance, via insulin resistance and the effects of adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…ANS dysregulation is reported to have a direct effect on BP regulation and lipid metabolism via circulating (nor) epinephrine (63)(64)(65)(66)(67). However, also more indirect ways are reported, for instance, via insulin resistance and the effects of adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the sympathetic tone has been reported to be associated with worsening of each pathophysiological component of MetS (26,27). Masuo et al demonstrated that elevation of the plasma norepinephrine levels preceded the development of insulin resistance and the elevation of blood pressure in their subjects (28).…”
Section: Discussionmentioning
confidence: 99%
“…We observed an increased AA concentration also in the aorta of rats after chronic swimming exercise which is associated with enhanced adrenergic influences [58]. This AA-raising effect of catecholamines appears to hold only for intact animals, because in cultured cardiomyocytes isoproterenol did not alter the fatty acid profile [25]. The pathogenetic relevance of AA is exemplified in patients with high risk for atherosclerosis on continuous ambulatory peritoneal dialysis [28].…”
Section: Inflammation and Eicosanoidsmentioning
confidence: 98%